FUNCTIONAL MODELING OF ACS USING THE MAEC-П PROGRAM - Tymovskiy А. К.; Goldobin О. О. (Radio Electronics, Computer Science, Control, 2011)
Functional modeling of automatic control systems using the programs of electronic circuits analysis.